ZIRCON GEOCHRONOLOGY AND METAMORPHIC EVOLUTION OF MAFIC DYKES IN THE HENGSHAN COMPLEX OF NORTHERN CHINA: EVIDENCE FOR LATE PALAEOPROTEROZOIC EXTENSION AND SUBSEQUENT HIGH-PRESSURE METAMORPHISM IN THE NORTH CHINA CRATON - Kröner A.; Wilde S.A.; Zhao G.C.; Sun M.; O'Brien P.J.; Liu D.Y.; Wan Y.S.; Liu S.W.; Guo J.H. (My University, 2006)
Magmatic and metamorphic zircons have been dated from ductilely deformed gabbroic dykes defining a dyke swarm and signifying crustal extension in the northern part of the Hengshan Complex of the North China Craton. These dykes now occur as boudins and deformed sheets within migmatitic tonalitic, trondhjemitic, granodioritic and granitic gneisses and are conspicuous due to relics of high-pressure granulite or even former eclogite facies garnet + pyroxene-bearing assemblages. SHRIMP ages for magmatic zircons from two dykes reflect the time of dyke emplacement at ~1915 Ma, whereas metamorphic zircons dated by both SHRIMP and evaporation techniques are consistently in the range 1848-1888 Ma. The youngest granitoid gneiss yet dated in the Hengshan has an emplacement age of 1872 ± 17 Ma. These results complement recent geochronological studies from the neighbouring Wutai and Fuping Complexes, to the SE of the Hengshan, showing that a crustal extension event occurred in the late Palaeoproterozoic. This preceded a major high-pressure collision-type metamorphic event in the central part of the North China Craton that occurred in the Palaeoproterozoic and not in the late Archaean as previously thought. Our data support recent suggestions that the North China Craton experienced a major, craton-wide orogenic event in the late Palaeoproterozoic after which it became cratonized and acted as a stable block. © 2006 Elsevier B.V. All rights reserved.
Keywords: HENGSHAN; MAFIC DYKE; METAMORPHISM; NORTH CHINA CRATON; PALAEOPROTEROZOIC; ZIRCON GEOCHRONOLOGY; Precambrian::Proterozoic::Paleoproterozoic; Докембрий::Протерозой::Палеопротерозойская